Bombs and Border Crossings: Peace Activist Networks and the Post-colonial State in Africa, 1959–62. (July 2015) - Skinner, Rob
This article explores the engagement between European, African and US peace activists as a case-study of the transnational dimensions of decolonization. Its focus is the protest against the first French nuclear weapons test in the Sahara, and European activists' involvement in subsequent international conferences in Ghana that sought to contest 'nuclear imperialism'. The article assesses the limits of transnationalism when addressing interconnected histories of European, African and US anti-nuclear weapons campaigns and argues that, rather than facilitating the formation of new transnational communities, anti-nuclear peace movements in Africa coalesced around pre-existing anti-colonial activist networks. Furthermore, this study of interactions between Western and African activists suggests that there is a need for greater reflection on the sometimes contradictory ways in which campaign groups have interacted with the nation-state and negotiated transnational connections in 'global' political spaces.